Fatigue analyses of self-piercing rivets and clinch joints in lap-shear specimens of aluminum sheets. (March 2015) - Su, Zheng-Ming; Lin, Pai-Chen; Lai, Wei-Jen; Pan, Jwo
Highlights: The SPRs and clinch joints showed different failure modes under different loading conditions. Dominant fatigue cracks of SPRs and clinch joints were identified. A fatigue model for SPRs and clinch joints based on structural stresses was first developed. The life estimations based on the model showed good agreement with the experimental results. Abstract: Fatigue behavior of self-piercing rivets (SPRs) and clinch joints in lap-shear specimens of 6111-T4 aluminum sheets with different thicknesses was investigated. Lap-shear specimens with SRPs and clinch joints were tested under quasi-static and cyclic loading conditions. Micrographs showed different failure modes of SPRs and clinch joints under different loading conditions. Dominant fatigue cracks were identified. The structural stress model from Tran and Pan's recent works was adopted. The structural stress solutions at the crack initiation locations and the stress-life data of aluminum 6111-T4 were adopted to estimate fatigue lives. The fatigue life estimations show good agreement with the experimental results.